Veterinary Clinic Management System - Ainin Sofea, Azhari (Universiti Malaysia Sarawak (UNIMAS), 2020)
This is a Veterinary Clinic Management System that being proposed for this project. The proposed system is being developed to solve the problems that facing by the most of veterinary clinics which are currently using traditional method in operating their organisations in manually or physical filling especially on their pets’ vaccination cards. This is because the method has some drawbacks such as the for pet vaccination card can be easily misplaced, missing or the pet owner would forget to bring them before going to veterinary clinics in order to get a vaccination and deworming services for their pets. Besides, the difficulty of the pet owner to make any appointment services for their pets by making a phone call or visit at the clinic is inconvenient for them. In addition, staff and veterinarian are unable to access the records of the patients(pet owner and pet) visiting the clinic. Thus, a web-based system and mobile application for pets’ vaccination card is being proposed to overcome the mentioned downsides. Veterinary Clinic Management System is a system that allows that pet owner to access their pets’ medical record, to request an online appointment and to receive a notification of the appointment. Not only it would be beneficial to the pet owners, it will also reduce the workload of veterinary clinic staff; especially in the management of files containing the pet owner and pets’ information as well as they able to generate daily, weekly or monthly clinic report for the patients(pet owner and pets) who comes to the clinics for the clinic references. For pet vaccination E-card mobile application, this apps is for pet owner to view the details of their pets’ vaccination appointment details such as the type of the vaccination and the next date for the vaccination and deworming services. The method used in the proposed system is the System Development Life Cycle (SDLC) model which consists of seven phases where each of the phase will be describes in the chapter of the reports.